Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/s2221-1691(11)60003-8
|View full text |Cite
|
Sign up to set email alerts
|

ETM study of electroporation influence on cell morphology in human malignant melanoma and human primary gingival fibroblast cells

Abstract: Asian Pac J Trop Biomed 2011; 1(2): 94-98

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
3
7
0
Order By: Relevance
“…However, recent mathematical calculations have shown that such pulses can actually have effects on internal membranes 49 . This theoretical model has been confirmed in vitro by our laboratory (unpublished data) and by others, although a 2-fold higher field amplitude was used in this latter study 50 . Hence, the microsecond electric pulses used in our study and in ECT might directly provoke CRT translocation to the cell membrane.…”
Section: Discussionsupporting
confidence: 77%
“…However, recent mathematical calculations have shown that such pulses can actually have effects on internal membranes 49 . This theoretical model has been confirmed in vitro by our laboratory (unpublished data) and by others, although a 2-fold higher field amplitude was used in this latter study 50 . Hence, the microsecond electric pulses used in our study and in ECT might directly provoke CRT translocation to the cell membrane.…”
Section: Discussionsupporting
confidence: 77%
“…As expected, immature cardiomyocytes show significantly lower viability threshold value of the pulse intensities than cells of other tissues treated by the same protocol (e.g. Saczko et al 2010;Skolucka et al 2011). The effect of EP above this pulse intensity can also be observed on phase contrast images of cells, obtained directly after EP.…”
Section: Discussionsupporting
confidence: 72%
“…The electro-photodynamic therapy applied to lung cancer cells (A549) revealed a significant increase of the cytotoxic effect on cells when compared to HpD-PDT alone, even at drug doses significantly lower than typical levels. The results also demonstrated that the drug was delivered within minutes, instead of hours as in standard PDT (Skolucka et al 2011). Labanauskiene et al (2009 examined Chinese hamster lung fibroblast cell line (DC-3F) (2007) and murine hepatoma MH22A cells.…”
Section: Discussionmentioning
confidence: 78%
“…The Epon blocks were cut on the ultramicrotome (Ultracut E, Reihert, Germany). Ultrathin sections were contrasted with uranyl acetate and lead citrate according to the method described by Skolucka et al (2011) and examined with a TEM Zeiss EM 900 (Carl Zeiss, Oberkochen, Germany).…”
Section: Transmission Electron Microscope (Tem)mentioning
confidence: 99%